Witchcraft narratives in Germany : Rothenburg 1561-1652 - Rowlands, Alison (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2003)
This text looks at why witch-trials failed to escalate into 'witch-crazes' in certain parts of early modern Europe. Using the legal records of Rothenburg ob der Tauber, the book explores the social and psychological conflicts behind the making of accusations and confessions of witchcraft.
Keywords: Witchcraft -- Germany -- Rothenburg ob der Tauber -- History -- 16th century.; Witchcraft -- Germany -- Rothenburg ob der Tauber -- History -- 17th century.; Sorcellerie -- Allemagne -- Rothenburg ob der Tauber -- Histoire -- 16e siècle.; Sorcellerie -- Allemagne -- Rothenburg ob der Tauber -- Histoire -- 17e siècle.; Humanities.; History.; Regional and national history.; European history.; BODY, MIND & SPIRIT -- Magick Studies.; BODY, MIND & SPIRIT -- Witchcraft & Wicca.; HISTORY -- Europe -- General.; Witchcraft; Germany -- Rothenburg ob der Tauber; Hexenverfolgung; Rothenburg ob der Tauber; Heksenprocessen.; Hekserij.; 1500-1699; Geschichte 1561-1652.; Multi-User.; Electronic books.; History